Simbioses de rizóbios com leguminosas arbóreas na pré-amazônia maranhense - Coelho, Katia Pereira (2016)
The tree leguminous gliricídia (Gliricidia sepium), acácia (Acacia mangium), leucena (Leucaena leucocephala) and sombreiro (Clitoria fairchildiana) are indicated for agroforestry systems, reclamation of degraded lands, reforestation and other purposes in the wet tropic. Despite the importance of legumes the preamazon region it is lacking in information about the symbiotic capacity and diversity of indigenous rhizobia of these legumes. The aim of this work was to evaluate the phenotypic and genetic diversity of rhizobia species nodulating gliricidia sombreiro, leucena and acacia in the Maranhão pre-Amazon region and authenticate isolates of these species in siratro (Macroptilium atropurpureum). For this they were installed two experiments. Sampling was carried out on a alley cropping system, was sampled 20 plants of each species by collecting 10 nodules per plant. It was made isolation, cultural characterization, partial 16S rRNA gene sequencing and analysis of the symbiotic ability of bacterial strains with siratro. The authentication experiment was done in two steps for each legume (gliricidia, acácia, sombreiro and leucena), in the greenhouse and in a completely randomized design with three replications with sterile Hoagland nutrient solution as substrate. Gliricídia, Sombreiro, leucena and acacia are colonized by distinct groups of rhizobia. Gliricidia nodulate preferably with Rhizobium, sombreiro and acacia nodulate preferably with Bradyrhizobium and leucena has Mesorhizobium main symbiote. Endophytic strains of ten genera were found colonizing the gliricidia, sombrero, leucena and acacia nodules and a strain of Arthrobacter sp. had a positive nodulation with siratro. This is the first report on isolation of Methylobacterium sp. in gliricidia nodules and endophytic ability of Terriglobus sp. strains. Indigenous strains of pre-Amazon region of Bradyrhizobium, Mesorhizobium and Rhizobium genus nodulate with siratro, but are ineficiente or had low efficiency to promote their growth.